Single-Domain Antibodies for Targeting, Detection, and In Vivo Imaging of Human CD4+ Cells - Traenkle, Bjoern; Kaiser, Philipp D.; Pezzana, Stefania; Richardson, Jennifer; Gramlich, Marius; Wagner, Teresa R.; Seyfried, Dominik; Weldle, Melissa; Holz, Stefanie; Parfyonova, Yana; Nueske, Stefan; Scholz, Armin M.; et al. (Frontiers in Immunology, 2021)
Abstract The advancement of new immunotherapies necessitates appropriate probes to monitor the presence and distribution of distinct immune cell populations. Considering the key role of CD4+ cells in regulating immunological processes, we generated novel single-domain antibodies (nanobodies, Nbs) that specifically recognize human CD4. After in depth analysis of their binding properties, recognized epitopes, and effects on T cell proliferation, activation and cytokine release, we selected CD4 specific Nbs that did not interfere with crucial T cell processes in vitro and converted them into immune tracers for non-invasive molecular imaging. By optical imaging, we demonstrate the ability of a high-affinity CD4-Nb to specifically visualize CD4+ cells in vivo using a xenograft model. Furthermore, quantitative high-resolution immune positron emission tomography (immunoPET)/MR of a human CD4 knock-in mouse model showed rapid accumulation of 64Cu-radiolabeled CD4-Nb1 in CD4+ T cell-rich tissues. We propose that the CD4 Nbs presented here could serve as versatile probes for stratifying patients and monitoring individual immune responses during personalized immunotherapy in both cancer and inflammatory diseases.